A HISTORICAL ANALYSIS ON THE GENEOLOGY AND THE TEACHING OF BULUGH AL-MARAM IN PESANTREN AL-MUNAWWIR KRAPYAK YOGYAKARTA INDONESIA (JOURNAL OF INDONESIAN ISLAM, 2014)
This article discusses the history of the teachings (kitab) of Bulugh al-Maram as they have developed in the pesantren tradition. It became popular in Indonesia since Indonesian Islam is generally of the Sunni-Syafi’i school. Aside from being influenced by the different streams of Islam that have made their way to Indonesia, Islamic scholars who have studied or worked in the Mecca and return to Indonesia with new knowledge continue to spread the teachings of the Syafi’i school of thought. The reputation of Ibn Hajar has been brought back by Indonesian Islamic scholars who have been to the Middle East. The effect of this movement of Islamic renewal has put pressure on the Al Quran and the Sunnah. There are three methods used in studying the kitab at the Pesantren Al-Munawwir in Krapyak. Firstly, the lecture method, which is a method practiced in most of the areas of study in this pesantren. Secondly, the question-answer method, in which the Kiai/Nyai invites santri to comment and ask questions about matters they do not yet understand. Thirdly, assignments method, in which one student is given the task of reading the Kitab Bulugh al-Maram min Adillat al-Ahkam aloud, and when a section is complete the other students give their interpretation of the text one by one.